THE RHYTHMIC GYMNASTICS IN UERJ - PERSPECTIVES OF WORK EXTENSION AND RESEARCH (Fiep Bulletin - online, 2014)
The Interdisciplinary Laboratory of Rhythmic Gymnastics with focus in Education and Health consists in a central region of concentration and integration, where studies related to rhythmic activities that are inherent to the human being will continue to be conducted. It's understandable that the University external community, in its geographic and social-cultural dimension, is the base of the actions in all the phases of the investigative process, planning, execution and evaluation. The Physical Education graduates are expected to be professionals that are synchronized with the moment and the place where they live, interacting with their social/cultural reality with reflexive and critical analysis capacity. All the actions of this Laboratory will have to be congregated in the optics of Health, through the study of the inherent activities connected to the practice of this sports modality and of the undeniable benefits that it offers the full development of the human body, and of its interaction with the Education. It is also intended, to provide the users a chance to act next to the external community, living their problems to discover solutions together. Methodology: To stimulate in the undergraduates of Physical Education bigger social, pedagogical and political experiences by means of activities that involve multiple disciplines and institutions, offering them an improvement of the learned pedagogical rules in the graduation course, to be used in the primary and secondary educational systems of our schools by means of a gradual social insertion in its profession. Results: Events that are extensive to other educational institutions and communities, as the “Encontro Escolar de GR” in its 19ª edition; the Symposiums of Extension, lectures; more than 20 research articles produced and published in congresses and similar events. Structuring physical adequacy and implementation of the new laboratory. Final considerations: The actions of the Nucleus/Laboratory have fomented the practice and the spreading of the modality in social entities of children and the primary and secondary educational system - public and private systems extending the professional possibilities of the Physical Education professionals.
Keywords: Laboratory; Education; Health